Kalanchoe sect. Socotranae (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae) circumscribed in the autonymic Kalanchoe subg. Kalanchoe - Smith, Gideon F. (Phytotaxa, 2026)
Situated in the Arabian Sea south of Yemen and east of the Gulf of Aden, the Socotra Archipelago has been finally separated from Africa for about 17 to 18 million years. The Archipelago, a UNESCO World Heritage Site, has high levels of biodiversity endemism. The genus Kalanchoe (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae) is represented in the Socotra Archipelago by three species, two of which, K. farinacea and K. robusta, are included in K. sect. Socotranae, a section in the autonymic K. subg. Kalanchoe. The section is here circumscribed.